Long non-coding RNA PSMA3-AS1 promotes glioma progression through modulating the miR-411-3p/HOXA10 pathway - Tianzao Huang; Yingxian Chen; Yile Zeng; Chaoyang Xu; Jinzhong Huang; Weipeng Hu; Xiangrong Chen; Huangde Fu (BMC Cancer, 2021)
Abstract Background Glioma is a common type of brain tumor and is classified as low and high grades according to morphology and molecules. Growing evidence has proved that long non-coding RNAs (lncRNAs) play pivotal roles in numerous tumors or diseases including glioma. Proteasome 20S subunit alpha 3 antisense RNA 1 (PSMA3-AS1), as a member of lncRNAs, has been disclosed to play a tumor-promoting role in cancer progression. However, the role of PSMA3-AS1 in glioma remains unknown. Therefore, we concentrated on researching the regulatory mechanism of PSMA3-AS1 in glioma. Methods PSMA3-AS1 expression was detected using RT-qPCR. Functional assays were performed to measure the effects of PSMA3-AS1 on glioma progression. After that, ENCORI ( http://starbase.sysu.edu.cn/ ) database was used to predict potential genes that could bind to PSMA3-AS1, and miR-411-3p was chosen for further studies. The interaction among PSMA3-AS1, miR-411-3p and homeobox A10 (HOXA10) were confirmed through mechanism assays. Results PSMA3-AS1 was verified to be up-regulated in glioma cells and promote glioma progression. Furthermore, PSMA3-AS1 could act as a competitive endogenous RNA (ceRNA) for miR-411-3p to regulate HOXA10 and thus affecting glioma progression. Conclusion PSMA3-AS1 stimulated glioma progression via the miR-411-3p/HOXA10 pathway, which might offer a novel insight for the therapy and treatment of glioma.